Neonatal Endocrinologic Problems in Collodion Babies. Issue 3 (May 2017) - Ozdemir, Ahmet; Korkut, Sabriye; Kurtoglu, Selim; Hatipoglu, Nihal; Gunes, Tamer; Ozturk, Mehmet Adnan
Abstract: Objectives: To identify endocrinologic problems, particularly those concerning growth, in collodion babies (CBs). Methods: Clinically identified newborn CBs were included in the study group (group 1). Because CBs are generally born premature, small for gestational age (SGA), or both, a control group matched to the study group in terms of gestational age and birthweight (group 2) was also established. Blood specimens were collected from both groups for thyroid function tests and to measure serum growth hormone (GH), insulinlike growth factor 1 (IGF‐1) and IGF binding protein‐3 (IGFBP‐3) levels. Results: Group 1 consisted of 42 CBs (25 male, 17 female) with gestational ages of 32 to 42 weeks and birthweights of 1, 400 to 4, 000 g. Twelve were assessed as premature and 17 as SGA. Serum IGF‐1 and IGFBP‐3 levels were lower and serum GH levels higher than in controls. Primary hypothyroidism was diagnosed in 10 patients in the study group, subclinical hypothyroidism in 2, and central hypothyroidism in 1. A statistically significant difference was determined between the groups in terms of primary hypothyroidism (p = 0.01). Serum GH levels were weakly negatively correlated with birthweight (correlation coefficient [ r ] = −0.32, p = 0.04) and serum IGF‐1 ( r = −0.38, p = 0.001) and IGFBP‐3 ( r = −0.36, p = 0.002) levels. Conclusion: Premature birth and SGA are common in CBs. GH levels are high and IGF‐1 and IGFBP‐3 levels low at birth as a sign of GH resistance in these patients. The greater prevalence of hypothyroidism in these children is also significant.